Kondisi Terkini Regulasi EMC dan Kesesuaian Produk di Indonesia - I Inayaturohman; D Hamdani; D Darwanto (Jurnal Teknologi Bahan dan Barang Teknik, 2014)
Electromagnetic compatibility (EMC) can be considered as the ability of the electromagnetic apparatus to function satisfactorily without interfering the others or being interfered by the others. Nowadays, the conformity of electromagnetic products to corresponding EMC standards becomes of importance in order to cope with the mandatory requirements prescribed by the global market. The EMC conformity becomes the main part of quality assurance and safety of products. This paper presents the state-of-the-art EMC conformity of products in Indonesia from regulation and technical point of view. We conducted survey on the quo-vadis of EMC regulation in the country by communicating with some governmental bodies. At the same time, we investigates the EMC conformity of some productsi.e. televisiom and refrigerator in domestic market by conducting EMC testing on them including emission and immunity test. From our investigation it is realized that regulations on EMC are not established yet because the responsible authorities are not assigned yet. Therefore EMC conformity is not mandatory yet for products manufactured or imported for domestic market. However, it is planned that the mandatory would come into power in earliest 2015. Moreover, EMC testing showed that the products under testing are mostly not conforming to EMC standards. Those products did not meet, either one of emission/immunity requirement or both. This fact emphasizes the need of establishing mandatory EMC regulation as well as responsible authorities. Kompatibilitas elektromagnetik (EMC) dapat dianggap kemampuan suatu peralatan yang tetap dapat berfungsi secara baik pada lingkungan Elektromagnetik tanpa mengganggu atau diganggu oleh peralatan lain. Saat ini, kesesuaian produk elektromagnetik terhadap standar EMC menjadi penting untuk mengatasi persyaratan wajib yang ditentukan oleh pasar global. Kesesuaian produk terhadap EMC menjadi bagian utama dari jaminan mutu dan keamanan produk-produk berkualitas.Makalah ini menyajikan kondisi saat ini (state-of-the-art). Kesesuaian EMC suatu produk di Indonesia terhadap peraturan dan sudut pandang teknis. Kami melakukan survei mengenai peraturan EMC di Indonesia dengan berkomunikasi dengan beberapa badan pemerintah. Pada saat yang sama, kami menyelidiki kesesuaian EMC beberapa produk seperti televisi dan refrigerator di pasar domestik dengan melakukan pengujian EMC untuk beberapa parameter emisi dan imunity.Dari hasil investigasi kami, perlu disadari bahwa peraturan EMC yang belum ada, dikarenakan kementerian yang bertanggung jawab belum mewajibkan. Oleh karena itu kesesuaian produk terhadap EMC masih belum wajib baik produk yang diproduksi atau diimpor untuk pasar domestik. Namun, direncanakan pemberlakuan wajib paling cepat pada tahun 2015. Selain itu, pengujian EMC menunjukkan bahwa produk yang diuji sebagian besar tidak sesuai dengan standar EMC. Produk-produk tersebut tidak memenuhi, salah satu dari emisi atau persyaratan imunitas atau bahkan keduanya. Fakta ini menekankan perlunya segera membuat peraturan EMC serta lembaga yang bertanggung jawab.